2018
DOI: 10.3136/fstr.24.129
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese Fermented Food Natto Inhibits Sucrose-dependent Biofilm Formation by Cariogenic Streptococci

Abstract: Our previous study indicated that certain commercially available proteases inhibit biofilm formation by cariogenic streptococci. Natto made from soybeans cultured with Bacillus subtilis natto contains an abundance of proteolytic enzymes. In this study, we investigated the correlation between the protease activity of extracts from 36 commercially available natto products and the inhibition of biofilm formation. The biofilm inhibitory effect was found to correlate with the level of protease activity in the natto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…This result was consistent with the inhibition of biofilm formation by commercially available subtilisin NAT: the presence of approximately 0.05 and 0.02 U/mL medium of commercially available subtilisin NAT reduced the safraninstained biofilm by about 80 % and 20 %, respectively (data not shown). These results strongly support our previous conclusion that subtilisin NAT is the biofilm inhibitor in natto extract (Iwamoto et al, 2018;Narisawa et al, 2014). Kitagawa et al (2017) showed that the natto peptide, which consists of 45 amino acid residues, has a bactericidal effect against Grampositive bacteria, such as S. pneumoniae and some Bacillus species; however, in our study, the natto extracts did not affect S. mutans growth in a liquid medium (Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This result was consistent with the inhibition of biofilm formation by commercially available subtilisin NAT: the presence of approximately 0.05 and 0.02 U/mL medium of commercially available subtilisin NAT reduced the safraninstained biofilm by about 80 % and 20 %, respectively (data not shown). These results strongly support our previous conclusion that subtilisin NAT is the biofilm inhibitor in natto extract (Iwamoto et al, 2018;Narisawa et al, 2014). Kitagawa et al (2017) showed that the natto peptide, which consists of 45 amino acid residues, has a bactericidal effect against Grampositive bacteria, such as S. pneumoniae and some Bacillus species; however, in our study, the natto extracts did not affect S. mutans growth in a liquid medium (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Natto, a fermented food product made from soybeans using Bacillus subtilis natto as a starter strain, is currently one of the most widely consumed fermented foods in Japan. In our previous study, a water-soluble fraction from a commercially available natto product interfered with the sucrose-dependent biofilm formation of S. mutans without reducing viable cell numbers (Iwamoto et al, 2018). Our results indicated that natto could be used as a safe functional food with anti-caries activity.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Kolodkin-Gal et al found that Bacillus subtilis inhibited the formation of bacterial biofilms and triggered the scattering of mature biofilms by synthesizing D-tyrosine, D-leucine, D-methionine, and D-tryptophan [ 18 ]. The study by Iwamoto et al stated that natto made from soybeans cultured with Bacillus subtilis natto inhibits the formation of biofilm [ 19 ]. The study of Martin et al showed that Bacillus Natto was able to destroy the preformed biofilm [ 20 ], which might explain the mechanism by which the probiotics used in our study worked.…”
Section: Discussionmentioning
confidence: 99%